2021
DOI: 10.17516/1998-2836-0255
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Development of Research of Composite Elastomer Materials

Abstract: The aim of this work is to study the effect of new modified ingredients on the complex of properties of composite elastomeric materials. It was found that the introduction of modified ingredients into the composition of elastomeric compositions enhances interfacial interaction at the «rubber-filler» interface and the formation of additional bonds between rubber macromolecules and functional groups, as a result of which an improvement in the complex of properties of the compositions is observed. The introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The higher the frequency, i.e. the shorter the exposure time, the higher will be the glass transition temperature of the plasticized system [1][2][3][4][5][6][7][8][9][10][11][12][13].  OFF-oligomer from furfural, OTHFS-oligomer of tetrahydrofurfuryl alcohol, OFFSoligomer from furfuryl alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the frequency, i.e. the shorter the exposure time, the higher will be the glass transition temperature of the plasticized system [1][2][3][4][5][6][7][8][9][10][11][12][13].  OFF-oligomer from furfural, OTHFS-oligomer of tetrahydrofurfuryl alcohol, OFFSoligomer from furfuryl alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of furan oligomers as plasticizers for elastomer compositions has shown that, being a product of a multifunctional action, they exhibit high plasticizing properties, while increasing the stickiness of rubber compounds and the strength properties of rubber. It has also been established that they significantly activate the process of both sulfuric and thiuramic vulcanization [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the discovery of the vulcanization process, the use of rubber was limited. It can be argued that only thanks to the discovery of vulcanization rubber has become a technically valuable material [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The essence of this process is determined by the peculiarities of dispersed systems, primarily, the particle size composition of solid particles and their volume concentration. The mutual influence of fluid and solid particles during their joint movement is detected by the wear of the pipeline materials, a kind of pressure loss and the determination of the bearing stream capacity [5][6][7][8][9]. The particle size distribution composition of solid particles of dispersed systems, as well as their concentration and modification, have an influence as a change in the average flow rate and as a result of the change in the hydraulic and energy parameters of the pressure system [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%